A 1.5-V 550-μW 176×144 autonomous CMOS active pixel image sensor. - Kwang-Bo Cho (IEEE Transactions on electron devices)
This paper addresses the development of a micropower 176×144 CMOS active pixel image sensor that dissipates one to two orders of magnitude less power than current state-of-the-art CMOS image sensors. The chip operates from a 1.5-V voltage source and the power consumption measured for the chip running from an internal 25.2-MHz clock yielding 30 frames per second is about 550 μW. This amount enables the sensor to run from a watch battery. In order to achieve design goals, a low-power sensor design methodology is applied throughout the design process from system-level to process-level, while realizing the performance to satisfy the design specification. As an autonomous sensor, it can be operated with only three pads [GND, VDD (1.2-1.7 V), DATAOUT]. The die occupies 4 mm2 of silicon.